Long Bone Mineral Loss, Bone Microstructural Changes and Oxidative Stress After Eimeria Challenge in Broilers - Tompkins, Y. H.; Teng, P.; Pazdro, R.; Kim, W. K. (Frontiers in Physiology, 2022)
The objective of this study was to evaluate the impact of coccidiosis on bone quality and antioxidant status in the liver and bone marrow of broiler chickens. A total of 360 13-day old male broilers (Cobb500) were orally gavaged and infected with different concentrations of Eimeria oocysts solution (negative control, low, medium-low, medium-high, and highest dose groups). Broiler tibia and tibia bone marrow were collected at 6 days post-infection (6 dpi) for bone 3-D structural analyses and the gene expression related to osteogenesis, oxidative stress, and adipogenesis using micro-computed tomography (micro-CT) and real-time RT-PCR analysis, respectively. Metaphyseal bone mineral density and content were reduced in respond to the increase of Eimeria challenge dose, and poor trabecular bone traits were observed in the highest challenge dose group. However, there were no significant structural changes in metaphyseal cortical bone. Medium-high Eimeria challenge dose significantly increased level of peroxisome proliferator-activated receptor gamma (PPARG, p<0.05) and decreased levels of bone gamma-carboxyglutamate protein coding gene (BGLAP, p<0.05) and fatty acid synthase coding gene (FASN, p<0.05) in bone marrow. An increased mRNA level of superoxide dismutase (SOD, p<0.05), heme oxygenase 1(HMOX1, p<0.05), and catalase (CAT, p<0.05), and increased enzyme activity of SOD (p<0.05) were found in bone marrow of Eimeria challenged groups compared with that of non-infected control. Similarly, enzyme activity of SOD and the mRNA level of SOD, HMOX1 and aflatoxin aldehyde reductase (AKE7A2) were increased in the liver of infected broilers, whereas glutathione (GSH) content was lower in the medium-high challenge group compared with non-challenged control. Moreover, the mRNA expression of catalase (CAT) and nuclear factor kappa B1 (NFKB1) showed dose-depend response in the liver, where expression of CAT and NFKB1 was upregulated in the low challenge group but gradually decreased with the higher Eimeria challenge dosage. In conclusion, Eimeria infection negatively affected the long bone development. The structural changes of tibia and decreased mineral content were mainly located at the trabecular bone of metaphyseal area. The change of redox and impaired antioxidant status following the Eimeria infection were observed in the liver and bone marrow of broilers.